A second-order adaptive DLN algorithm with different subdomain variable time steps for the 3D closed-loop geothermal system - Chen, Lele; Qin, Yi; Gao, Xinyue; Wang, Yang; Li, Yi; Li, Jian (Computers & mathematics with applications (1987), 2024)
In this paper, we propose a second-order adaptive DLN algorithm with different subdomain variable time steps for the 3D closed-loop geothermal system. Theoretically, the stability and convergence of the algorithm in the case of variable time steps are analyzed. In numerical experiments, the DLN algorithm is combined with an adaptive algorithm to verify not only its effectiveness and second-order convergence under any arbitrary sequence of time steps but also to improve computational efficiency. We overcome the difficulty of 3D programming, and verify the applicability and accuracy of the proposed algorithm by simulating the flow characteristics and heat transfer of the closed-loop geothermal system with 3D convection.